Mean Platelet Volume and Thrombocytopenia as Hematological Predictive Indicator of Patients’ Outcome in Medical Intensive Care Unit (Medical Forum Monthly, 2024)
Objective: The present study determined the predictive significance of mean platelet volume (MPV) and low platelet count (thrombocytopenia) as hematological indicator of patient outcome in medical intensive care units (ICU).Study Design: Observational study.Place and Duration of Study: This study was conducted at the Department of Pathology and Medical ICU, Indus Medical College Hospital, Tando Muhammad Khan, Sindh from April 2017 to March 2019.Materials and Methods: Critical subjects admitted to medical intensive care units of the hospital were selected according to inclusion and exclusion criteria. A sample of 300 (n=300) patients was selected and analyzed to meet criteria of study. 5-10 ml of venous blood sample was collected for study parameters. Data was analyzed on SPSS 21.0 IBM, Incorporation USA at 95% confidence interval.Results: Thrombocytopenia was noted in 70 (23%) and severe thrombocytopenia in 19 (6.3%) patients (P=0.0001). Thrombocytopenia and severe thrombocytopenia were noted in 14 (4.6%) of non- survivors vs. (1.6%) in survivors (P=0.0001). Normal and elevated MPV in survivors and non- survivors were noted in 195 (65%) vs. 40 (13.3%) and 14 (4.6%) vs. 51 (17%) respectively (P-0.0001). Platelet counts and MPV in survivors and non- survivors were noted as 378457±459 vs. 123153±366 (x109/L) (P=0.0001) and 9.83±1.23 vs. 14.73±3.53 fl respectively (P=0.0001). ROC curve shows area under curve (AUC) of 0.913 (91.3%) (P=0.0001).Conclusion: Thrombocytopenia and elevated MPV are useful hematological indicators to predict the poor patient outcome and mortality.